PERLINDUNGAN HUTAN MELALUI SISTEM VERIFIKASI LEGALITAS KAYU (SVLK) DALAM PRESPEKTIF ISLAM - Wattimena, Abd Khair (IAIN Tulungagung, 2018)
ABSTRACTTimber legality assurance system (TLAS) is determined by the Ministry of Forestry to stop illegal logging. TLAS is the government instrument to guarantee that just legal timber/wood which are permitted to be harvested, delivered, manufactured, and sold/ marketed in Indonesia. This system is in line with the forestry law maintenance direction to fight” illegal logging” and “illegal timber trading”. The issue of Indonesian TLAS is the initiative of many components of society since 2001 such as NGO, civil society, traditional right holders, ntrepreneur/privatesector,academist/university, government and all stakeholders who are aware on the forest continuity. TLAS is one effort to prevent the forest destruction. Viewing from the Islamic concept, TLAS is following the Fiqh conception: Daf’ul mafasadah muqoddam ala jalbi al maslahah. To prevent forests from distruction is also prescribed in holy Qur’an, surah Ar Rum ayat 41: “.....have everseen the distruction in land and in the sea because of human hands activities”. In this context, TLAS is one form of good governance forest management and is legal according to positive law and Islamic law. This system must be supported by the society, so that the idea to free from illegal logging and illegal timber can be realized.Keywords: Distruction Forestry, Timber Legality Assurance System, Islam Conseption